Knight fever : towards an economics of awards - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2005)
Awards in the form of orders, medals, decorations and titles are ubiquitous in monarchies and republics, private organizations, not-for-profit and profit-oriented firms. Nevertheless, economists have disregarded this kind of non-material extrinsic incentive. The demand for awards relies on an individual's desire for distinction, and the supply of awards on the provision of incentives. Relative price and income effects are shown to be identifiable and strong. A number of empirically testable propositions are formulated. As awards are (at least so far) impossible to measure adequately, empirical tests are carried out using the technique of analytic narratives.
Keywords: Z13; L22; J33; J22; D73; D23; 330; incentives; motivation; awards; orders; distinction; principal-agent; Preisverleihung; Leistungsanreiz; Sozialer Status; Leistungsmotivation; Agency Theory; Theorie